Thrombo-Inflammation in Cardiovascular Disease: An Expert Consensus Document from the Third Maastricht Consensus Conference on Thrombosis - d’Alessandro, Elisa; Becker, Christian; Bergmeier, Wolfgang; Bode, Christoph; Bourne, Joshua H.; Brown, Helena; Buller, Harry R.; ten Cate-Hoek, Arina J.; ten Cate, Vincent; van Cauteren, Yvonne J. M.; Cheung, Yam F. H.; Cleuren, Audrey; Coenen, Danielle; Crijns, Harry J. G. M.; de Simone, Ilaria; Dolleman, Sophie C.; Klein, Christine Espinola; Fernandez, Delia I.; Granneman, Lianne; van t Hof, Arnoud; Henke, Peter; Henskens, Yvonne M. C.; Huang, Jingnan; Jennings, Lisa K.; Jooss, Natalie; Karel, Mieke; van den Kerkhof, Danique; Klok, Frederik A.; Kremers, Bram; Lämmle, Bernhard; Leader, Avi; Lundstrom, Annika; Mackman, Nigel; Mannucci, Pier M.; Maqsood, Zahra; van der Meijden, Paola E. J.; van Moorsel, Marc; Moran, Luis A.; Morser, John; van Mourik, Manouk; Navarro, Stefano; Neagoe, Raluca A. I.; Olie, Renske H.; van Paridon, Pauline; Posma, Jens; Provenzale, Isabella; Reitsma, Pieter H.; Scaf, Billy; Schurgers, Leon; Seelig, Jaap; Siegbahn, Agneta; Siegerink, Bob; Soehnlein, Oliver; Soriano, Eva Maria; Sowa, Marcin A.; Spronk, Henri M. H.; Storey, Robert F.; Tantiwong, Chukiat; Veninga, Alicia; Wang, Xueqing; Watson, Steve P.; Weitz, Jeff; Zeerleder, Sacha S.; ten Cate, Hugo; Scientific Reviewer Committee; Badimon, Lina; Binder, Christoph; Hoylaerts, Marc; Karlheinz, Peter; Koenen, Rory; Lip, Gregory Y. H.; Massberg, Steffen; von Hundelshausen, Philipp; Weber, Christian; Wojta, Johann (Thrombosis and Haemostasis, 2020)
Thrombo-inflammation describes the complex interplay between blood coagulation and inflammation that plays a critical role in cardiovascular diseases. The third Maastricht Consensus Conference on Thrombosis assembled basic, translational, and clinical scientists to discuss the origin and potential consequences of thrombo-inflammation in the etiology, diagnostics, and management of patients with cardiovascular disease, including myocardial infarction, stroke, and peripheral artery disease. This article presents a state-of-the-art reflection of expert opinions and consensus recommendations regarding the following topics: (1) challenges of the endothelial cell barrier; (2) circulating cells and thrombo-inflammation, focused on platelets, neutrophils, and neutrophil extracellular traps; (3) procoagulant mechanisms; (4) arterial vascular changes in atherogenesis; attenuating atherosclerosis and ischemia/reperfusion injury; (5) management of patients with arterial vascular disease; and (6) pathogenesis of venous thrombosis and late consequences of venous thromboembolism.
Keywords: thrombosis; inflammation; coagulation; pulmonary embolism; myocardial infarction; stroke; platelets